Outcome of Pregnancies with Fibroids and its Associated Complications: A Prospective Study - Swarna Sudha Pullemalla; B. Bhargavi (Asian Journal of Medical Research, 2020)
Background: Fibroids (leiomyomas) are benign smooth muscle cell tumors of the uterus. Although they are extremely common, with an overall incidence of 40% to 60% by age 35 and 70% to 80% by age 50, the precise etiology of uterine fibroids remains unclear. Some studies have shown a relationship between uterine fibroids and pregnancy complications, such as preterm birth, premature rupture of membranes (PROM), fetal malpresentation, placental abruption and intrauterine fetal demise. The aim is to study the outcome of pregnancies with fibroids and their associated complications. Materials and methods: The present study was conducted in the Department of Gynecology in a tertiary care hospital. For the study, a total of 40 patients were selected between the age range of 21 to 45 years from the outpatient list of the department of gynecology with pregnancy with fibroid after attending first-trimester ultrasonography examination which diagnosed them. The patients underwent both consequent antenatal care and delivery at the study institute in the study time. Ultrasonogram was done at successive visits to evaluate the change in the size of the fibroid and any associated complications either in fibroid or in pregnancy in general. Results: We observed that 15 patients had threatened miscarriage, 12 had preterm labor, 2 had antepartum bleeding, 3 had abdominal pain needing admission, 2 had laparotomy due to pain, 1 had a postpartum hemorrhage and only one patient needed a blood transfusion. Spontaneous abortion was observed in 2 patients, premature delivery in 15, delivery at 37-41 weeks in 37, vaginal delivery in 5 patients and cesarean section in 44 patients. Conclusion: Within the limitations of the present study, it can be concluded that pregnant women diagnosed with uterine fibroids are at a greater risk of complication during the antepartum, intrapartum, and postpartum periods.